Factores psicológicos, académicos y socioeconómicos asociados a la permanencia, deserción y reintegro en la educación superior (2024)
University studies represent a fundamental milestone in social and personal development in contemporary society. However, a significant proportion of young people who enter the higher education system either suspend or do not complete their studies due to multiple factors. In this context, persistence, dropout, and re-enrollment emerge as phenomena that impact students, institutions, and society, making it necessary to investigate them. The objective of this research was to analyze the psychological, academic, and socioeconomic factors associated with persistence, dropout, and re-enrollment in higher education. A quantitative approach with a descriptive-correlational and cross-sectional design was used. The sample consisted of 947 students and former students from the American University Institution of Barranquilla, classified as dropouts (51.53%), re-enrolled (24.29%), and persistent students (24.18%). Data collection was carried out retrospectively, using information from the Student Characterization instrument applied in the 2023-1 period through the "Adviser" platform, which includes a comprehensive evaluation of socioeconomic, psychological, and academic elements of students enrolled each academic period. The results showed significant differences in socioeconomic, psychological, and academic characteristics between students who persist, drop out, and re-enroll in university studies. The main difference was found in economic conditions, levels of motivation, and academic performance. Students who persist in their studies have fewer economic limitations, higher academic performance, and intrinsic motivation styles. In contrast, students who drop out face greater economic limitations, academic difficulties, and extrinsic motivation. Finally, it was found that students who temporarily leave their studies but later re-enroll have economic resources, academic performance, and motivation at intermediate levels between the persistence and dropout groups. These results highlight key aspects to consider in addressing the issue of dropout, institutional policies promoting re-enrollment, and strategies that ensure persistence.